إصلاح اسواق المشتقات المالية غير المنظمة : ضرورة حتمية لاجتناب أزمات مالية مستقبلية - حسيبة، سميرة (جامعة الأمير عبد القادر للعلوم الإسلامية, 2014)
تعد المشتقات المالية أبرز المبتكرات المالية التي صاحبت التطورات الحاصلة في النظام المالي العالمي, وهي منتجات تمتاز بالمرونة والتعقيد وتقدم تغطية جيدة ضد المخاطر, لكنها تحولت إلى أدوات للمجازفة ونقل المخاطر, خاصة أثناء الأزمة المالية العالمية 2008 حيث كانت وراء إفلاس العديد من المؤسسات المالية, الأمر الذي استدعى إعادة النظر في تنظيم أسواق المشتقات المالية خاصة تلك التي تتم خارج المقصورة (التفاوض بالتراضي) وذلك بإخضاع العقود الأكثر تجانساً للمقاصة المركزية والإبلاغ عنها لدى دلائل مركزية للمعلومات من أجل تحقيق انضباط السوق واجتناب أزمات مالية مستقبلية قد تقود العالم إلى وجهة مجهولة. Financial derivatives products are presented as one of the most important financial innovations that have accompanied the evolution of the global financial system, products are characterized by flexibility and complexity, and provide a good hedge against risks, but they have become a source of speculation and contagion risk , especially during the global financial crisis of 2008. they were behind the collapse of many financial institutions. Which necessitated the reform of the regulation of derivatives markets, particularly those treated OTC (over-the-counter), this reform will affect derivatives sufficiently standardized that will necessarily offset by a central counterparty (CCP), the recording of all transactions within the central data registers (trade repositories-TR) and the establishment of international unique identifier (legal entity identifyer-LEI) to achieve market discipline, and to avoid future financial crises that will lead the world to a destination unknown.
Keywords: المشتقات المالية -- الأزمة المالية -- مبادلات خطر عدم السداد